OPTIMIZING EDUCATIONAL EXCELLENCE: THE DYNAMIC IMPACT OF TRANSFORMATIVE LEADERSHIP ON TEACHER AND STUDENT PERFORMANCETHROUGH INNOVATION AND COLLABORATION - Ignatius Septo Pramesworo; Loso Judijanto; Yance Manoppo; Elvi Rahmi; M. Yemmardotillah (International Journal of Teaching and Learning, 2023)
In pursuing educational excellence, this study delved into the dynamic impact of transformative leadership on teacher and student performance, emphasizing innovation and collaboration. Employing a comprehensive mixed-methods research design, the research explored the multifaceted dimensions of transformative leadership in the educational context. Data collection involved surveys to quantify perceptions and in-depth interviews to capture nuanced insights, ensuring a holistic understanding of leadership dynamics. The findings revealed that transformative leadership significantly influenced teachers, fostering heightened dedication and professional growth. Students, in turn, experienced a more enriching learning environment, leading to improved academic outcomes and socio-emotional well-being. The study also identified collaborative decision-making and supportive school culture as pivotal within the transformative leadership paradigm.